A sandwich-type sulfur cathode based on multifunctional ceria hollow spheres for high-performance lithium–sulfur batteries. (19th March 2019) - Wang, Jianwei; Zhou, Bo; Zhao, Hongyang; Wu, Miaomiao; Yang, Yaodong; Sun, Xiaolei; Wang, Donghai; Du, Yaping
Abstract : CeO2 hollow spheres are prepared to fabricate the inside and outside structures of cathodes by a simple layer-by-layer process. Abstract : Despite prominent research efforts towards developing cathode materials for lithium–sulfur batteries, relatively little emphasis has been placed on constructing functional cathode architectures. Herein, ceria (CeO2 ) hollow spheres are prepared to fabricate the inside and outside structures of cathodes. A sandwich-type sulfur cathode, namely, a h-CeO2 /sulfur- x -CNT/h-CeO2 cathode, is designed and fabricated by a simple layer-by-layer process. Due to its unique structural and compositional features, the h-CeO2 /sulfur-0.8-CNT/h-CeO2 cathode delivers high specific capacities of 876, 761, and 644 mA h g −1 at 1C, 2C and 5C rates, and the capacity retentions are 85.7%, 87.8%, and 92.4%, respectively. During 100 test cycles, the material displays high coulombic efficiencies (above 99%) after the first cycle. More importantly, the cathode with a sulfur loading of 1.8 mg cm −2 also exhibits a stable cycling life up to 500 cycles at 1C with a capacity decay as low as 0.073% per cycle.